A Study on Leadership Competencies of the Generation Z in a VUCA World - Dr. Shaheema Hameed, Dr. Vandana Sharma (International Journal of Advanced Science and Technology, 2020)
The study researches the various aspects of the leadership competencies of the Generation Z in a VUCA setting. Given the rapid rate of change today, the research was conducted to study the leadership competencies of the youngest workforce (the Generation Z) and their preparedness for facing demanding jobs in VUCA organizational settings. Studies show that a competency based approach towards leadership accounts for better identification and progress of leaders in the workforce. The study was conducted on a sample of 300 respondents that are employed or on internships and who belong to the Generation Z cohort. A structured questionnaire using the leadership competency model developed by (McCauley, 2009) and Global Competencies perspective (McHall & Hollenbeck, 2002)was used for measuring the leadership competencies among the sample. The results were arrived at after conducting Multiple Regression Analysis. Results reveal that the Generation Z are competent to lead the organizations but are not competent enough to handle leading themselves and leading others. The findings also reveal that Global Leadership competencies which are considered essential for a VUCA world are not inherent in the Generation Z. The paper contributes to academics and industry practitioners by presenting findings that are exclusive to the Generation Z cohort. This facilitates the formulation of strategies that are conducive in industries for the induction and training of the Generation Z.